High-performance stable lithium battery composite diaphragm and preparation method thereof
By using a multi-bend fiber base film combined with inorganic nanocoating on the lithium battery separator, the problem of insufficient thermal safety of the separator and lithium ion conduction capability is solved, and a high-performance and stable lithium battery separator is realized, which enhances the battery Thermal stability and electrochemical properties.
Patent Information
- Application Number
- CN202411437303.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium battery separators are prone to thermal safety problems due to heat shrinkage or fuse under overcharge/over-discharge or extreme conditions, and the existing inorganic coatings lack lithium ion conduction capabilities, which may cause the battery to catch fire or explode.
The design of combining multi-curved pore fiber base film and inorganic nanocoating is adopted. By coating the inorganic nanocoating layer composed of raw materials such as silicate nanocomposites on the multi-curved pore fiber base film, the porosity and liquid absorption of the membrane are improved. and mechanical properties, and enhance coating adhesion through plasma discharge treatment.
It significantly improves the thermal stability, chemical stability and electrochemical properties of the lithium battery separator, enhances the lithium ion conduction ability, ensures good mechanical properties and electrolyte wetting at high temperatures, and reduces the risk of explosion and fire.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy materials, and in particular to a high-performance and stable lithium battery composite diaphragm and a preparation method thereof. Background Art
[0002] Since the concept of rechargeable lithium batteries was proposed in the early 1970s, and since the birth and commercialization of lithium-ion batteries, due to their superior performance, they have quickly become a research hotspot in multiple disciplines such as advanced energy, materials, and electrochemistry, and are widely used in small electronic devices and medical devices such as laptops, mobile phones, digital cameras, mp3 players, etc. as a driving power source.
[0003] Lithium-ion batteries have high energy density and cycle life, and are one of the preferred batteries for power devices and high-capacity electronic products. However, under extreme conditions of overcharge / overdischarge or other improper use, the temperature inside the lithium battery will rise rapidly, causing damage to the diaphragm, battery fire or explosion. Commonly used lithium battery diaphragms are mainly polyolefin polymer materials such as polypropylene (PP) and polyethylene (PE). These materials have high tensile strength and electrolyte wettability, but due to the need for pore formation during the preparation process, there is generally a stretching and pore expansion process. Even at higher temperatures that do not reach the glass transition temperature, there is a tendency to rebound, causing thermal shrinkage or diaphragm melting, leading to thermal safety problems; or a nano-inorganic oxide particle coating bonded by an inert polymer binder is coated on the surface of the diaphragm, but the inorganic particles in the existing inorganic coating slurry are mostly dense particles, which do not have lithium ion conductivity. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a high-performance and stable lithium battery composite diaphragm and a preparation method thereof, so as to solve the problem of effectively improving the porosity and liquid absorption rate of the diaphragm while having good mechanical properties and thermal stability.
[0005] The technical solution adopted by the present invention is as follows: a high-performance and stable lithium battery composite diaphragm, which mainly includes a multi-porous fiber-based membrane and an inorganic nano-coating coated on the surface of the multi-porous fiber-based membrane, wherein the inorganic nano-coating is composed of the following raw materials in parts by weight: 47-65 parts of silicate nanocomposite, 10-20 parts of binder, 1-6 parts of emulsifier, and 15-25 parts of solvent; The multi-porous fiber-based membrane is a polyvinylidene fluoride / polyurethane two-component nanofiber membrane.
[0006] Preferably, the silicate nanocomposite is formed by crystallizing a composite of a montmorillonite interlayer polymerized modified body and ultra-high molecular weight polyethylene in a mass ratio of (1-10):100.
[0007] Preferably, the multi-porous fiber-based membrane is prepared by the following method: adding polyvinylidene fluoride and a blocked polyurethane prepolymer in a mass ratio of 100:(5-20) to an electrospinning solvent, stirring and dissolving at 50-60°C to obtain a co-spinning solution with a mass fraction of 8-20%; loading the co-spinning solution into an electrospinning device for electrospinning to obtain an ultrafine fiber non-woven membrane; treating the ultrafine fiber non-woven membrane at 150-200°C for 15-20min, and then treating it at 100-120°C for 30-120min to unblock the blocked polyurethane prepolymer, and then placing it at room temperature and an air humidity of 50-70% for 1-3 days to obtain the multi-porous fiber-based membrane.
[0008] Preferably, the electrospinning parameters are: spinning temperature 20-40°C, spinning relative humidity 30-60%, spinning voltage 10-30KV, receiving distance 10-20cm, solution flow rate 0.2-2ml / h, receiver speed 100-500rpm; the electrospinning solvent is a mixed solvent with a mass ratio of DMF / N-methylpyrrolidone of (1-3):1.
[0009] Preferably, the closed polyurethane prepolymer is prepared by the following method: a polyurethane prepolymer and toluene in a mass ratio of 3:1 are put into a three-necked reaction bottle, mixed evenly, and then caprolactam is dissolved in toluene, wherein the molar ratio of the polyurethane prepolymer to caprolactam is 1:(1-1.5), and then the mixture is added dropwise to the reaction bottle with stirring, the reaction temperature is raised to 70-90°C, and the reaction is carried out at a constant temperature for 3-6 hours to obtain a closed polyurethane prepolymer.
[0010] Preferably, the silicate nanocomposite is prepared by the following method: sodium montmorillonite is put into a flask reactor containing ethanol, and after stirring and dispersing for 1-3 hours, an ethanol solution of hexadecyltrimethylammonium bromide with a mass fraction of 8-20% is added dropwise into the flask reactor with stirring, and reacted at a temperature of 55-70°C for 1-2 hours to obtain a mixture; styrene is added dropwise to the mixture, and stirred at high speed for 0.5-2 hours to obtain a montmorillonite suspension; then dibenzoyl peroxide is added to the montmorillonite suspension, and the mass ratio of sodium montmorillonite, styrene and dibenzoyl peroxide is (2-8): (10-15): 1, and stirred at low speed for 3-6 hours. After the polymerization is completed, the reaction product is filtered, vacuum dried, and ground to obtain a montmorillonite interlayer polymerized modified body; the montmorillonite interlayer polymerized modified body and ultra-high molecular weight polyethylene with a mass ratio of (1-10): 100 are mixed, and then put into an internal mixer, and granulated by screw extrusion to obtain the silicate nanocomposite.
[0011] Preferably, the banburying conditions are: banburying temperature is 200-240° C., rotation speed is 45-65 r / min, and banburying time is 10-20 min.
[0012] Preferably, the binder is a copolymer adhesive of vinyl pyrrolidone and vinyl acetate (PVP-VA); the emulsifier is one or a mixture of two or more of polyethylene castor oil derivatives, polyvinyl pyrrolidone, polyvinyl alcohol, carboxymethyl cellulose, methyl cellulose, lecithin; and the solvent is one or a mixture of two or more of acetone, ethyl acetate, dichloromethane or triethyl phosphate.
[0013] Preferably, the inorganic nano coating has a thickness of 0.5-10 μm.
[0014] A method for preparing a high-performance and stable lithium battery composite diaphragm comprises the following steps: Step 1, preparing a porous fiber-based membrane and a silicate nanocomposite respectively; Step 2: Add the emulsifier, solvent, binder and silicate nanocomposite into a reaction kettle, and mix them at a rotation speed of 500-20000 for 0.5-2h to obtain an inorganic nano coating slurry; Step 3: Place the porous fiber-based membrane into the reaction chamber of the plasma treatment device, evacuate to a vacuum degree of 2-4 Pa, use oxygen as the replacement gas, generate plasma by radio frequency inductive coupling after replacement, and perform plasma excitation for 60-90 seconds at a power of 100-200 W and a radio frequency of 12-14 MHz to obtain a plasma surface-treated porous fiber-based membrane.
[0015] Step 4: Apply the coating to the surface of the porous fiber-based membrane obtained in step 3 by scraping, rolling or spraying, and dry at 60-80° C. to obtain a high-performance and stable lithium battery composite separator.
[0016] Beneficial effects: Compared with the prior art, the present invention provides a high-performance and stable lithium battery composite diaphragm and a preparation method thereof, which adopts the method of coating an inorganic nano-coating on the surface of a porous fiber-based membrane to ensure that the composite diaphragm has good mechanical properties and conductivity, while improving the thermal stability of the diaphragm. The porous fiber-based membrane is a two-component nanofiber membrane obtained by the co-spinning treatment of a polyvinylidene fluoride / polyurethane blend system. The polyvinylidene fluoride and polyurethane in the membrane exist in the form of fibers at the same time, and have high liquid absorption rate, porosity and strong ion conductivity. After heat treatment, the polyurethane fibers are bonded together to increase the force per unit cross-sectional area and improve the tensile strength of the fiber membrane; the silicate nanocomposite contained in the inorganic nano-coating is dissociated into small crystals under strong shearing during the melt intercalation process of montmorillonite modified by interlayer polymerization and ultra-high molecular weight polyethylene, and then the polyethylene macromolecular chains are inserted into the montmorillonite interlayer, resulting in the layered structure of the montmorillonite. The ordered structure is destroyed and evenly dispersed in polyethylene. The silicate nanocomposite as the main component of the inorganic nano coating can improve the thermal dimensional stability and thermal safety of the diaphragm. At the same time, the coating has a higher ability to conduct lithium ions than traditional coatings, which can improve the electrical performance of lithium batteries and have stronger lithium ion conductivity of lithium battery diaphragms. In the preparation process, O2 plasma discharge treatment is used to introduce oxygen-containing functional groups on the polymer surface, improve the wettability of the diaphragm, and interrupt the CC on the polymer surface, ablate the short-chain molecules on its surface, remove the amorphous and crystalline areas on the polymer surface to a certain extent, and improve the adhesion between the multi-porous fiber-based membrane and the inorganic nano coating. The present invention has high ionic conductivity, good thermal stability, chemical stability and electrochemical stability, and maintains high wettability to the electrolyte and excellent mechanical properties during repeated charging and discharging. DETAILED DESCRIPTION
[0017] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below in conjunction with specific implementation methods.
[0018] Example 1 Preparation of high performance and stable lithium battery composite separator I Step 1, preparation of porous fiber-based membrane: put polyurethane prepolymer and toluene in a mass ratio of 3:1 into a three-necked reaction bottle, mix evenly, then dissolve caprolactam in toluene, wherein the molar ratio of polyurethane prepolymer to caprolactam is 1:1, and then add it dropwise into the reaction bottle with stirring, the reaction temperature rises to 70-90°C, and the reaction is carried out at a constant temperature for 3-6 hours to obtain a blocked polyurethane prepolymer; add polyvinylidene fluoride and blocked polyurethane prepolymer in a mass ratio of 100:5, DMF / The method comprises the following steps: a) treating the superfine fiber non-woven membrane at 150°C for 15-20min and then treating the superfine fiber non-woven membrane at 100°C for 30-120min to unblock the blocked polyurethane prepolymer and then placing the pre-polymer at room temperature and an air humidity of 50-70% for 1-3 days to obtain the multi-porous fiber-based membrane.
[0019] Preparation of silicate nanocomposites: sodium montmorillonite is put into a flask reactor containing ethanol, and after stirring and dispersing for 1-3 hours, an ethanol solution of 8% by mass of hexadecyltrimethylammonium bromide is added dropwise to the flask reactor under stirring, and reacted at a temperature of 55-70°C for 1-2 hours to obtain a mixture; styrene is added dropwise to the mixture, and stirred at high speed for 0.5-2 hours to obtain a montmorillonite suspension, and then dibenzoyl peroxide is added to the montmorillonite suspension, and sodium montmorillonite, styrene and dibenzoyl peroxide are added to the montmorillonite suspension. The mass ratio of formyl is 2:10:1, and the mixture is stirred at a low speed for 3-6 hours. After the polymerization is completed, the reaction product is filtered, vacuum dried, and ground to obtain a montmorillonite interlayer polymerization modified body; the montmorillonite interlayer polymerization modified body and ultra-high molecular weight polyethylene with a mass ratio of 1:100 are mixed and put into an internal mixer. The internal mixer conditions are as follows: the internal mixer temperature is 200-240°C, the rotation speed is 45-65r / min, the internal mixer time is 10-20min, and the silicate nanocomposite is obtained by screw extrusion granulation.
[0020] Step 2: Add 1 part of emulsifier, 15 parts of solvent, 10 parts of binder and 47 parts of silicate nanocomposite into a reaction kettle, and mix at a speed of 500-20000 for 0.5-2h to obtain an inorganic nano coating slurry; Step 3: Place the porous fiber-based membrane into the reaction chamber of the plasma treatment device, evacuate to a vacuum degree of 2Pa, use oxygen as the replacement gas, generate plasma by radio frequency inductive coupling after replacement, and perform plasma excitation for 60-90s at a power of 100W and a radio frequency of 12MHz to obtain a plasma surface-treated porous fiber-based membrane.
[0021] Step 4: Apply the coating to the surface of the porous fiber-based membrane obtained in step 3 by scraping, rolling or spraying, and dry at 60-80° C. to obtain a high-performance and stable lithium battery composite separator.
[0022] Performance characterization: The tensile strength of the high-performance and stable lithium battery composite membrane prepared in this embodiment is 34 MPa, the elongation at break is 57.5%, the thermal shrinkage at 150°C is 1.5%, and the ionic conductivity is 6.5×10 -3 S·cm-1.
[0023] Example 2 Preparation of high performance and stable lithium battery composite separator II Step 1, preparation of porous fiber-based membrane: put polyurethane prepolymer and toluene in a mass ratio of 3:1 into a three-necked reaction bottle, mix evenly, then dissolve caprolactam in toluene, wherein the molar ratio of polyurethane prepolymer to caprolactam is 1:1.5, then add it dropwise into the reaction bottle with stirring, the reaction temperature rises to 70-90°C, and the reaction is carried out at a constant temperature for 3-6 hours to obtain a closed polyurethane prepolymer; add polyvinylidene fluoride and closed polyurethane prepolymer in a mass ratio of 100:20, DMF / The method comprises the following steps: dissolving the N-methylpyrrolidone in a mixed solvent with a mass ratio of 3:1 under stirring at 50-60°C to obtain a co-spinning solution with a mass fraction of 20%; loading the co-spinning solution into an electrospinning device for electrospinning to obtain an ultrafine fiber non-woven membrane, wherein the electrospinning parameters are: spinning temperature 40°C, spinning relative humidity 60%, spinning voltage 30KV, receiving distance 20cm, solution flow rate 2ml / h, and receiver speed 100-500rpm; treating the ultrafine fiber non-woven membrane at 200°C for 15-20min, and then treating it at 120°C for 30-120min to unblock the blocked polyurethane prepolymer, and then placing it at room temperature and air humidity of 50-70% for 1-3 days to obtain the multi-porous fiber-based membrane.
[0024] Preparation of silicate nanocomposites: sodium montmorillonite is put into a flask reactor containing ethanol, and after stirring and dispersing for 1-3 hours, a 20% by mass fraction of hexadecyltrimethylammonium bromide ethanol solution is added dropwise into the flask reactor under stirring, and reacted at a temperature of 55-70°C for 1-2 hours to obtain a mixture; styrene is added dropwise to the mixture, and stirred at high speed for 0.5-2 hours to obtain a montmorillonite suspension, and then dibenzoyl peroxide is added to the montmorillonite suspension. Sodium montmorillonite, styrene and dibenzoyl peroxide are added to the montmorillonite suspension. The mass ratio of formyl is 8:15:1, and the mixture is stirred at a low speed for 3-6 hours. After the polymerization is completed, the reaction product is filtered, vacuum dried, and ground to obtain a montmorillonite interlayer polymerization modified body; the montmorillonite interlayer polymerization modified body and ultra-high molecular weight polyethylene with a mass ratio of 10:100 are mixed and put into an internal mixer. The internal mixer conditions are as follows: the internal mixer temperature is 200-240°C, the rotation speed is 45-65r / min, the internal mixer time is 10-20min, and the silicate nanocomposite is obtained by screw extrusion granulation.
[0025] Step 2: Add 6 parts of emulsifier, 25 parts of solvent, 20 parts of binder and 65 parts of silicate nanocomposite into a reaction kettle, mix at a speed of 500-20000 for 0.5-2h to obtain an inorganic nano coating slurry; Step 3: Place the porous fiber-based membrane into the reaction chamber of the plasma treatment device, evacuate to a vacuum degree of 4 Pa, use oxygen as the replacement gas, generate plasma by radio frequency inductive coupling after replacement, and perform plasma excitation for 60-90 seconds at a power of 200 W and a radio frequency of 14 MHz to obtain a plasma surface-treated porous fiber-based membrane.
[0026] Step 4: Apply the coating to the surface of the porous fiber-based membrane obtained in step 3 by scraping, rolling or spraying, and dry at 60-80° C. to obtain a high-performance and stable lithium battery composite separator.
[0027] Performance characterization: The tensile strength of the high-performance and stable lithium battery composite membrane prepared in this embodiment is 41 MPa, the elongation at break is 56.8%, the thermal shrinkage at 150°C is 0.5%, and the ionic conductivity is 7.1×10 -3 S cm -1 .
[0028] Example 3 Preparation of high performance and stable lithium battery composite separator III Step 1, preparation of porous fiber-based membrane: put polyurethane prepolymer and toluene in a mass ratio of 3:1 into a three-necked reaction bottle, mix evenly, then dissolve caprolactam in toluene, wherein the molar ratio of polyurethane prepolymer to caprolactam is 1:1.1, then add it dropwise into the reaction bottle with stirring, the reaction temperature rises to 70-90°C, and the reaction is carried out at a constant temperature for 3-6 hours to obtain a closed polyurethane prepolymer; add polyvinylidene fluoride and closed polyurethane prepolymer in a mass ratio of 100:15, DMF / The method comprises the following steps: a) dissolving the N-methylpyrrolidone in a mixed solvent with a mass ratio of 1.5:1 under stirring at 50-60°C to obtain a co-spinning solution with a mass fraction of 12%; b) loading the co-spinning solution into an electrospinning device for electrospinning to obtain an ultrafine fiber non-woven membrane, wherein the electrospinning parameters are as follows: a spinning temperature of 25°C, a spinning relative humidity of 50%, a spinning voltage of 15KV, a receiving distance of 12cm, a solution flow rate of 0.3ml / h, and a receiver speed of 100-500rpm; b) treating the ultrafine fiber non-woven membrane at 150°C for 15-20min and then at 110°C for 30-120min to unblock the blocked polyurethane prepolymer, and then placing the membrane at room temperature and an air humidity of 50-70% for 1-3 days to obtain the multi-porous fiber-based membrane.
[0029] Preparation of silicate nanocomposites: sodium montmorillonite is put into a flask reactor containing ethanol, and after stirring and dispersing for 1-3 hours, a 15% ethanol solution of hexadecyltrimethylammonium bromide is added dropwise to the flask reactor under stirring, and reacted at a temperature of 55-70°C for 1-2 hours to obtain a mixture; styrene is added dropwise to the mixture, and stirred at high speed for 0.5-2 hours to obtain a montmorillonite suspension, and then dibenzoyl peroxide is added to the montmorillonite suspension. Sodium montmorillonite, styrene and dibenzoyl peroxide are added to the montmorillonite suspension. The mass ratio of formyl is 6:12:1, and the mixture is stirred at a low speed for 3-6 hours. After the polymerization is completed, the reaction product is filtered, vacuum dried, and ground to obtain a montmorillonite interlayer polymerization modified body; the montmorillonite interlayer polymerization modified body and ultra-high molecular weight polyethylene with a mass ratio of 5:100 are mixed and put into an internal mixer. The internal mixer conditions are as follows: the internal mixer temperature is 200-240°C, the rotation speed is 45-65r / min, the internal mixer time is 10-20min, and the silicate nanocomposite is obtained by screw extrusion granulation.
[0030] Step 2: 4 parts of emulsifier, 18 parts of solvent, 12 parts of binder and 58 parts of silicate nanocomposite are put into a reaction kettle, and mixed at a speed of 500-20000 for 0.5-2h to obtain an inorganic nano coating slurry; Step 3: Place the porous fiber-based membrane into the reaction chamber of the plasma treatment device, evacuate to a vacuum degree of 3Pa, use oxygen as the replacement gas, generate plasma by radio frequency inductive coupling after replacement, and perform plasma excitation for 60-90s at a power of 150W and a radio frequency of 14MHz to obtain a plasma surface-treated porous fiber-based membrane.
[0031] Step 4: Apply the coating to the surface of the porous fiber-based membrane obtained in step 3 by scraping, rolling or spraying, and dry at 60-80° C. to obtain a high-performance and stable lithium battery composite separator.
[0032] Performance characterization: The tensile strength of the high-performance and stable lithium battery composite membrane prepared in this embodiment is 45 MPa, the elongation at break is 58.2%, the thermal shrinkage at 150°C is 0.1%, and the ionic conductivity is 7.8×10 -3 S cm -1 .
[0033] Finally, it should be noted that the above description is only a preferred embodiment of the present invention. Under the guidance of the present invention, those skilled in the art can make a variety of similar expressions without violating the purpose and claims of the present invention, and such changes all fall within the protection scope of the present invention.
Claims
1. A high-performance and stable lithium battery composite diaphragm, characterized in that: It comprises a porous fiber-based membrane and an inorganic nano-coating coated on the surface of the porous fiber-based membrane, wherein the inorganic nano-coating is composed of the following raw materials in parts by weight: 47-65 parts of silicate nano-composite, 10-20 parts of binder, 1-6 parts of emulsifier, and 15-25 parts of solvent; The multi-porous fiber-based membrane is a polyvinylidene fluoride / polyurethane two-component nanofiber membrane.
2. The high-performance and stable lithium battery composite diaphragm according to claim 1, characterized in that: The silicate nanocomposite is composited by a montmorillonite interlayer polymerized modified body and ultra-high molecular weight polyethylene in a mass ratio of (1-10):
100.
3. The high performance and stable lithium battery composite diaphragm according to claim 1, characterized in that The multi-porous fiber-based membrane is prepared by the following method: adding polyvinylidene fluoride and blocked polyurethane prepolymer in a mass ratio of 100:(5-20) into an electrospinning solvent, stirring and dissolving at 50-60° C. to obtain a co-spinning solution with a mass fraction of 8-20%; The co-spun fiber solution is loaded into an electrospinning device for electrospinning to obtain an ultrafine fiber non-woven membrane; the ultrafine fiber non-woven membrane is treated at 150-200°C for 15-20 minutes, and then at 100-120°C for 30-120 minutes to unblock the blocked polyurethane prepolymer, and then placed at room temperature and an air humidity of 50-70% for 1-3 days to obtain the multi-porous fiber-based membrane.
4. The high-performance and stable lithium battery composite diaphragm according to claim 3, characterized in that: The electrospinning parameters are: spinning temperature 20-40°C, spinning relative humidity 30-60%, spinning voltage 10-30KV, receiving distance 10-20cm, solution flow rate 0.2-2ml / h, receiver speed 100-500rpm; the electrospinning solvent is a mixed solvent with a mass ratio of DMF / N-methylpyrrolidone of (1-3):
1.
5. The high performance and stable lithium battery composite separator according to claim 3, characterized in that The closed polyurethane prepolymer is prepared by the following method: a polyurethane prepolymer and toluene in a mass ratio of 3:1 are put into a three-necked reaction bottle, mixed evenly, and then caprolactam is dissolved in toluene, wherein the molar ratio of the polyurethane prepolymer to caprolactam is 1:(1-1.5), and then the mixture is added dropwise to the reaction bottle with stirring, the reaction temperature is raised to 70-90°C, and the reaction is carried out at a constant temperature for 3-6 hours to obtain a closed polyurethane prepolymer.
6. The high performance and stable lithium battery composite separator according to claim 1, characterized in that The silicate nanocomposite is prepared by the following method: sodium montmorillonite is put into a flask reactor containing ethanol, and after stirring and dispersing for 1-3 hours, an ethanol solution of hexadecyltrimethylammonium bromide with a mass fraction of 8-20% is added dropwise into the flask reactor with stirring, and reacted at a temperature of 55-70°C for 1-2 hours to obtain a mixture; styrene is added dropwise into the mixture, and stirred at high speed for 0.5-2 hours to obtain a montmorillonite suspension; dibenzoyl peroxide is added to the montmorillonite suspension, and the mass ratio of sodium montmorillonite, styrene and dibenzoyl peroxide is (2-8): (10-15): 1, and stirred at low speed for 3-6 hours. After the polymerization is completed, the reaction product is filtered, vacuum dried, and ground to obtain a montmorillonite interlayer polymerized modified body; the montmorillonite interlayer polymerized modified body and ultra-high molecular weight polyethylene with a mass ratio of (1-10): 100 are mixed, and then put into an internal mixer, and granulated by screw extrusion to obtain the silicate nanocomposite.
7. The high performance and stable lithium battery composite separator according to claim 6, characterized in that: The operating conditions in the internal mixer are: internal mixing temperature of 200-240° C., rotation speed of 45-65 r / min, and internal mixing time of 10-20 min.
8. The high performance and stable lithium battery composite separator according to claim 1, characterized in that: The binder is one or more of polyvinyl alcohol, polyacrylamide, and polypyrrolidone; the emulsifier is one or a mixture of two or more of polyvinyl castor oil derivatives, polyvinyl pyrrolidone, polyvinyl alcohol, carboxymethyl cellulose, methyl cellulose, and lecithin; and the solvent is one or a mixture of two or more of acetone, ethyl acetate, dichloromethane, or triethyl phosphate.
9. The high-performance and stable lithium battery composite separator according to claim 8, characterized in that: The inorganic nano coating has a thickness of 0.5-10 μm.
10. A method for preparing a high-performance and stable lithium battery composite diaphragm according to any one of claims 1 to 9, characterized in that The following steps are involved: Step 1, preparing a porous fiber-based membrane and a silicate nanocomposite respectively; Step 2: Add the emulsifier, solvent, binder and silicate nanocomposite into a reaction kettle, and mix them at a rotation speed of 500-20000 for 0.5-2h to obtain an inorganic nano coating slurry; Step 3: Place the porous fiber-based membrane into a reaction chamber of a plasma treatment device, evacuate to a vacuum degree of 2-4 Pa, use oxygen as a replacement gas, generate plasma by radio frequency inductive coupling after replacement, and perform plasma excitation for 60-90 seconds at a power of 100-200 W and a radio frequency of 12-14 MHz to obtain a plasma surface-treated porous fiber-based membrane; Step 4: Apply the coating to the surface of the porous fiber-based membrane obtained in step 3 by scraping, rolling or spraying, and dry at 60-80° C. to obtain a high-performance and stable lithium battery composite separator.
Citation Information
Patent Citations
Enhanced bi-component nanofiber porous membrane and preparation method thereof
CN102140734A
Hypervolume stable lithium battery and preparation method thereof
CN109346655A
Method for preparing nano composite material of polyethylene / montmorillonite
CN1563168A
Cited By
Heat-resistant ceramic coated diaphragm and preparation method thereof
CN121601959A